NGHIÊN CỨU ĐÁNH GIÁ TÁC ĐỘNG CỦA TRƯỜNG THỦY ĐỘNG LỰC ĐẾN ĐỊA HÌNH ĐÁY BIỂN ĐẢO NAM YẾT - TRƯỜNG SA - Khương, Văn Long; Nguyễn, Đình Hải; Lê, Văn Tuấn; Hoàng, Văn Thành (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
RESEARCH ASSESSMENT THE IMPACT OF THE HYDRODYNAMIC FIELDS ON THE SEABED TOPOGRAPHY OF NAMYIT ISLAND OF TRUONG SA ISLANDSThis research assesses the impact of major marine hydrodynamic factors, such as waves, currents, and sea levels on the changing processes of the seabed topography and the coastlines of the Namyit (Nam Yết) Island of ​​Truong Sa (Spratly) Islands, based on a many continuous years-data set. The study uses MIKE model to calculate and simulate the impact of wave field and current field on the process of accretion and erosion that changes the topography of the seabed. The results show that when comparing between calculated wave height, speed of the currents, and sea level height and those observed on scene are 69.1%, 54.5%, and 95.4% respectively. These figures meet the requirement of Nash Sutcliffe Efficiency, in which calculated sea level shows highest reliability. The research results provide an overview of wave and currents regimes in Northeast and Southwest monsoon seasons, and the characteristics of the current seabed topography around Namyit Island. The changing of seabed around Namyit Island includes diversified accretion and erosion. In the area from the depth of 10 m to the Island’ coastlines, the accretion dominant, with sediment thickness of up to 2.0 m. At 200 m West and East of the island, there have erosion areas, with sediment thickness reduces to 1.0 m. The changing of natural seabed topography of the researched area is mainly impacted by the process of accretion and erosion of sediment due to hydrodynamic regimes (waves, currents, and sea levels fluctuations) and the development and decline of seabed coral system. The research results are the scientific basis for planning, and proposing the construction around the island, planning for navigation channels dredging, and providing information for naval training, exercises, and operations around offshore islands.